Priorities in accommodating office user preferences: impact on office users decision to stay or go. Issue 2 (2014) - ,; ,
Abstract : Purpose – When current accommodation is unsatisfactory, office organisations consider relocating to new accommodation that optimally facilitates their main processes and supports image and financial yield. However, due to high vacancy levels, public opinion and governmental awareness oppose new office construction. Reusing existing buildings could be the egg of Columbus. This paper aims at answering the questions: which property characteristics are important push and pull factors for relocation? What does this mean for the decision: stay or go?Design/methodology/approach – A literature review of factors determining organisations' accommodation choices was conducted. Interviews were held with large‐scale office organisations and creative organisations, discussing relocation drivers. Henceforth, a survey was held among creative organisations, collecting data about property characteristics important for their preferences. Finally, office user preferences were compared with characteristics of structurally vacant buildings.Findings – Traditional push factors like car accessibility, extension need, and location and building image remain important. Nowadays sustainability issues like reducing energy consumption and better public transportation accessibility are highly prioritised pull factors as well. Regarding the creative industries, bike‐ and public transportation accessibility, multi‐tenancy, and ICT and meeting facilities are most important.Practical implications – Knowing office users' preferences is important to attract and retain stable tenants. If office space supply is highly aligned to end‐users' demands and easily adaptable to changing needs, probably more organisations will decide to stay instead of go, leaving behind empty offices.Originality/value – This study combines data about push and pull factors with relocation decision‐making, innovatively focussing on the creative industries. The data can be used to explore opportunities and risks of adaptive re‐use of the existing building stock. Acknowledgements : The authors would like to thank Robbert Arkenbout and Tim Hendrikx for the contribution to the data collection and data analyses as part of their graduation theses on this subject.